2014
DOI: 10.1093/annhyg/met078
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Transition Metals in Welding Fumes Using Paper-Based Analytical Devices

Abstract: Metals in particulate matter (PM) are considered a driving factor for many pathologies. Despite the hazards associated with particulate metals, personal exposures for at-risk workers are rarely assessed due to the cost and effort associated with monitoring. As a result, routine exposure assessments are performed for only a small fraction of the exposed workforce. The objective of this research was to evaluate a relatively new technology, microfluidic paper-based analytical devices (µPADs), for measuring the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Several research groups have reported the colorimetric detection of Cr(VI) using μ-PADs based on the specific reaction with 1,5-diphenylcarbazide (DPC) [27][28][29][30][31][32][33][34]. In early studies, Rattanarat et al and Cate et al used an online oxidation reaction with Ce(IV) to present colorimetric measurements of total Cr [30,31]. We also demonstrated a remote investigation of total Cr in environmental samples from Ethiopia using μ-PADs [32].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Several research groups have reported the colorimetric detection of Cr(VI) using μ-PADs based on the specific reaction with 1,5-diphenylcarbazide (DPC) [27][28][29][30][31][32][33][34]. In early studies, Rattanarat et al and Cate et al used an online oxidation reaction with Ce(IV) to present colorimetric measurements of total Cr [30,31]. We also demonstrated a remote investigation of total Cr in environmental samples from Ethiopia using μ-PADs [32].…”
Section: Introductionmentioning
confidence: 64%
“…When the solution reached the detection zones by capillary action, the immediate appearance of a purple color was visible to the naked eye. The original amount of Cr(VI) reacted with 1,5-DPC to form a colored complex in the left channels [31,37,38] whereas the total Cr(IV), which included additional Cr(VI) that originated from the online oxidation of Cr(III) by Ce(IV), produced a purple color in the right channels.…”
Section: Colorimetric Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…With paper-based devices, samples can be tested closer to or at the site of contamination, reducing the cost and time associated with heavy metal detection. For example, sample digestion can be performed on a filter membrane with nitric acid and a low-power microwave . Using this digestion method, sample has been analyzed colorimetrically, electrochemically, and by distance .…”
Section: Device Designs and Modificationsmentioning
confidence: 99%
“…For example, sample digestion can be performed on a filter membrane with nitric acid and a low-power microwave . Using this digestion method, sample has been analyzed colorimetrically, electrochemically, and by distance . Pretreatment zones are often incorporated directly into devices as well.…”
Section: Device Designs and Modificationsmentioning
confidence: 99%